Comparison on the abundance of pollinating weevil (Elaeidobius kamerunicus) in immature and mature of oil palm (Elaeis guineensis) - Din, Muhamad Zia Hul Haq (2016)
Elaeidobius kamerunicus is a pollinating weevil of oil palm from the Order coleoptra was introduced and imported from Africa to improved pollination and increased fruit set for oil palm plantations in Malaysia. It was successfully established in Malaysia oil palm plantation in the middle of 1981. The aim of this study were: 1) to determine the abundance of E. kamerunicus on the male and female inflorescences; 2) to compare the population of E. kamerunicus in immatured and matured oil palm; and 3) to investigate the relationship of temperature and relative humidity (RH) pattern with the abundance of E. kamerunicus. This sampling was conducted in immature oil palm (less than 5 years) and matured oil palm (more than 5 years) in different plots. From each plot, 5 male and female inflorescences were randomly. For each male inflorescences, five spikelets were randomly chosen from each upper, middle and lower level of the inflorescent. Each male chosen spikelet were covered with plastic to prevent the escape of the wevils. All the spikelets were cut and brought to the laboratory for further investigation. While the female inflorescences flower, the weevils were sampled by using aspirator. The temperature and relative humidity were taken three times for each different age plot by using Data Logger. In this study,there was a significant difference (P<0.05) in the abundance of E. kamerunicus between sampling time in male inflorescences while in female inflorescences there was no significant difference (P>0.05). The abundance of E. kamerunicus was not significantly different between the immature and mature oil palm. The abundance of E. kamerunicus shows that the highest in number when there wa low relative humidity.